FDOPA Patterns in Adrenal Glands: A Pictorial Essay. (May 2017) - Moreau, Aurélie; Giraudet, Anne Laure; Kryza, David; Borson-Chazot, Françoise; Bournaud-Salinas, Claire; Mognetti, Thomas; Lifante, Jean-Christophe; Combemale, Patrick; Giammarile, Francesco; Houzard, Claire
Abstract : Abstract: 18 F-FDOPA is a well-established tool to explore pheochromocytomas. It tends to replace 123 I-MIBG scan in metastatic pheochromocytomas, multiple endocrine neoplasia type 2-related tumors, succinate dehydrogenase [ubiquinone] iron-sulfur subunit-negative tumors, and succinate dehydrogenase[ZERO WIDTH SPACE]-positive lesions. To our knowledge, no study has characterized physiological and pathological adrenal glands with 18 F-FDOPA from a quantitative point of view. We report the features of different normal and pathological adrenal glands with 18 F-FDOPA. Within our series, only pheochromocytomas present a significantly increased uptake reflecting the high specificity of this tracer. Tumors such as adenomas or myelolipomas present no 18 F-FDOPA significant accumulation. Interestingly, adrenal gland hyperplasia and solitary glands do not demonstrate compensatory uptake.